Śmierć ćmy - Woolf, Virginia (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The image of moths gathering around a source of light recurs in Woolf’s private writings and becomes an import motif also in her novels and essays. It is most probably the description of moths in her sister’s letter that become an initial inspiration for writing of The Waves, Woolf’s most radical experiment in novelistic form, where she strives to create a subject-less perspective. On the other hand The Death of The Moth, a 1927 essay, whose first translation into Polish comes together with the present commentary from the translator, is a crystal-clear description of the world as seen by the writer/narrator at her desk, surrounded by exuberant life but witnessing death.